2012
DOI: 10.1111/j.1467-8691.2012.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility in Innovation: Insights from two Cases of Syngenta's Activities in Genetically Modified Organisms

Abstract: Corporate social responsibility (CSR) implies that companies have collective responsibility beyond legal requirements. This ‘beyond’ can be described along the ‘triple bottom line’ of sustainability (social, environmental and economic dimensions). Dealing with these dimensions is under discussion in societies and some propose the stakeholder concept as a framework for companies to identify their responsibilities. However, who counts as a key stakeholder and what is a legitimate stake are difficult to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The final purpose is to assign the importance levels to the indicators to be consequently usable for the decision-making process. In order to verify the appropriateness on the indicators' list and to make sure that the identified indicators are practically applicable, a pilot survey was carried out through semi-structured interviews with six experts (DM 1 , DM 2 DM 3 , DM 4 , DM 5 and DM 6 ) involved in Edible Oil product projects in India. The characteristics required to define an individual as an "expert" are equivocal, according to [90].…”
Section: Identify and Finalize The Related Evaluation Criteria And Almentioning
confidence: 99%
See 4 more Smart Citations
“…The final purpose is to assign the importance levels to the indicators to be consequently usable for the decision-making process. In order to verify the appropriateness on the indicators' list and to make sure that the identified indicators are practically applicable, a pilot survey was carried out through semi-structured interviews with six experts (DM 1 , DM 2 DM 3 , DM 4 , DM 5 and DM 6 ) involved in Edible Oil product projects in India. The characteristics required to define an individual as an "expert" are equivocal, according to [90].…”
Section: Identify and Finalize The Related Evaluation Criteria And Almentioning
confidence: 99%
“…Authors in [5] found that up to 2014, 18 million farmers of 28 countries were able to cultivate over 181 million hectares of GM yields. GM yields with enhanced tolerance to pests and conservation stresses may reduce the use of chemical pesticides in the production of agricultural yields [6]. Moreover, because of their advanced yields, such crops may limit deforestation in developing countries and can preserve biodiversity [7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations